Redução de um ideal - Santos, Maxwell da Paixão de Jesus (2018)
In this work, under the view of commutative algebra, we will study reductions of an ideal, the concept was introduced by Northcott and Rees. First of all, we will give preliminary no- tions about dimension theory, Hilbert’s polynomial, Hilbert-Samuel’s polynomial, regularity of modules and superficial elements. Next we will discuss the main theme of this dissertation, where we will talk about integral closure of ideal, reduction and the Rees algebra, moreover, we will establish connections between these concepts. Finally, we will discuss some applica- tions in Hilbert-Samuel's polynomial and multiplicity theory, in which some recent results will be presented.